Separating the influence of the cortex and foam on the mechanical properties of porcupine quills - Yang, Wen; McKittrick, Joanna (Acta biomaterialia, 2013)
Lightweight thin cylinders filled with a foam have applications as collapsible energy absorbers for crashworthy and flotation applications. The local buckling compressive strength and Young’s modulus are dependent on material and geometrical properties. Porcupine quills have a thin cortex filled with closed-cell foam, and are entirely composed of α-keratin. The cortex carries the majority of the compressive load, but the foam is able to accommodate and release some of the deformation of the cortex during buckling. The presence of the foam increases the critical buckling strength, buckling strain and elastic strain energy absorption over that of the cortex. Good agreement is found between experimental results and modeled predictions. A strain distribution map of the foam close to the buckled cortex demonstrates that the deformation of the cells plays an important role in accommodating local buckling of the cortex. The robust connection between the foam and cortex results in superior crushing properties compared to synthetic sandwich structure where the foam normally separates from the shell. The foam/cortex construction of the quill can guide future biomimetic fabrications of light weight buckle-resistant columns.